Lexical Category of Style Markers Variations in Literary Self-Translation - Nugroho, Andy Bayu; Laksman, Myrna (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
This study aims to reveal the variations of the lexical category of the style markers in a self-translation from English to Indonesian and their roles in expressing the perceptions of the self-translator. This is a pilot research with a qualitative approach. The data are obtained from the novel The Question of Red (TQOR) and its Indonesia translation, Amba. In this context, Laksmi Pamuntjak acts as both the ST writer and the TT producer (as a self-translator). TQOR and Amba use lexical style markers that are not exactly the same, involving variations. The variations of the lexical category of style markers can be classified into: marker reduction, attribute reduction, marker transposition, marker extension, and invariation of marker. This variations are the impacts of the use of various translation strategies, which in turn also change the perception of self-translator of the themes she wants to express.